Photovoice as Project Based Learning to Foster Students’ Viewing and Writing Skills - Lily Juniarti; Fadila Nur Aulia Rahman; Siti Rahma Rusdianti; Tasya Fauziah Pupitawati (Universitas Suryakanca, 2022)
This study is aimed to explore the implementation of photovoice as project-based learning to develop students’ skills of viewing and exposition writing. It also investigates their viewing and writing development as well as their responses toward the photovoice as PBL. In conducting this study, a qualitative case study was used. The subjects of this research were a teacher and fifteen students from one of the Islamic senior high schools in Cianjur, West Java. The data were collected from observation, interviews, text analysis, and open-ended questionnaires. The findings revealed that photovoice was implemented as project-based learning through several stages. Initially, the students were stimulated with photos to show them that the photos could voice an issue. In terms of exposition writing skills, the students have developed their schematic structure, coherence, and language use. Furthermore, they gave positive responses to photovoice as PBL activities by showing enthusiasm and active involvement in class. Besides, they admitted that photovoice as PBL facilitated them to be more creative and communicative in expressing ideas and opinions from social phenomena that exist around them.Keywords: photovoice; PBL (project-based learning); exposition text; writing; viewing